Pelatihan Manajemen Produksi dan Pemasaran Digital bagi Peternak Ayam Petelur dan Kalkun di Dusun Karang, Desa Tuksono, Kecamatan Sentolo, Kabupaten Kulon Progo, Yogyakarta - Amir Hamzah; Renna Yanwastika Ariyana; Untung Joko Basuki (Yayasan Kajian Riset dan Pengembangan RADISI, 2026)
The development of digital technology and the internet requires businesses, including livestock businesses, to adapt to improve their performance and sustainability. Laying hen and turkey farmers in Karang Hamlet, Tuksongo Village, Sentolo District, as community service partners, face production management challenges such as feed control, livestock health, financial management, and traditional marketing management. One of these challenges stems from the low digital literacy of owners and employees. With 440 laying hens and 50 turkeys, all operational and marketing management has not yet utilised digital technology. This community service activity aims to improve the understanding and application of digital literacy in production and marketing management. The methods used include training in the application of digital applications in production management and marketing design using the internet and social media. The results of the activity indicate an increase in the understanding of farm owners and managers in production management (85%) and digital marketing management (90%). This increased understanding of digital literacy has proven to improve production aspects and better preparedness for development in marketing aspects.